3D Interconnected Magnetic Nanowire Networks as Potential Integrated Multistate Memristors - Bhattacharya, Dhritiman; Chen, Zhijie; Jensen, Christopher J.; Liu, Chen; Burks, Edward C.; Gilbert, Dustin A.; Zhang, Xixiang; Yin, Gen; Liu, Kai (Nano letters, 2022)
Interconnected magnetic nanowire (NW) networks offer a promising platform for three-dimensional (3D) information storage and integrated neuromorphic computing. Here we report discrete propagation of magnetic states in interconnected Co nanowire networks driven by magnetic field and current, manifested in distinct magnetoresistance (MR) features. In these networks, when only a few interconnected NWs were measured, multiple MR kinks and local minima were observed, including a significant minimum at a positive field during the descending field sweep. Micromagnetic simulations showed that this unusual feature was due to domain wall (DW) pinning at the NW intersections, which was confirmed by off-axis electron holography imaging. In a complex network with many intersections, sequential switching of nanowire sections separated by interconnects was observed, along with stochastic characteristics. The pinning/depinning of the DWs can be further controlled by the driving current density. These results illustrate the promise of such interconnected networks as integrated multistate memristors.